A brief history of bananas - Ng, F.S.P (UTAR Agriculture Science Journal, 2015)
BANANAS are the most popular of tropical fruits. Native to tropical Asia, they were spread in cultivation to Africa about 3000 years ago and to America after Columbus. However, banana origins in tropical Asia are shrouded in mystery.